Neutralizing Antibody Response to Pseudotype Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Differs Between mRNA-1273 and BNT162b2 Coronavirus Disease 2019 (COVID-19) Vaccines and by History of SARS-CoV-2 Infection. (20th December 2021) - Tyner, Harmony L; Burgess, Jefferey L; Grant, Lauren; Gaglani, Manjusha; Kuntz, Jennifer L; Naleway, Allison L; Thornburg, Natalie J; Caban-Martinez, Alberto J; Yoon, Sarang K; Herring, Meghan K; Beitel, Shawn C; Blanton, Lenee; et al.
Abstract: Background: Data on the development of neutralizing antibodies (nAbs) against SARS-CoV-2 after SARS-CoV-2 infection and after vaccination with mRNA COVID-19 vaccines are limited. Methods: From a prospective cohort of 3975 adult essential and frontline workers tested weekly from August 2020 to March 2021 for SARS-CoV-2 infection by reverse transcription–polymerase chain reaction assay irrespective of symptoms, 497 participants had sera drawn after infection (170), vaccination (327), and after both infection and vaccination (50 from the infection population). Serum was collected after infection and each vaccine dose. Serum-neutralizing antibody titers against USA-WA1/2020-spike pseudotype virus were determined by the 50% inhibitory dilution. Geometric mean titers (GMTs) and corresponding fold increases were calculated using t tests and linear mixed-effects models. Results: Among 170 unvaccinated participants with SARS-CoV-2 infection, 158 (93%) developed nAbs with a GMT of 1003 (95% confidence interval, 766–1315). Among 139 previously uninfected participants, 138 (99%) developed nAbs after mRNA vaccine dose 2 with a GMT of 3257 (2596–4052). GMT was higher among those receiving mRNA-1273 vaccine (GMT, 4698; 3186–6926) compared with BNT162b2 vaccine (GMT, 2309; 1825–2919). Among 32 participants with prior SARS-CoV-2 infection, GMT was 21 655 (14 766–31 756) after mRNA vaccine dose 1, without further increase after dose 2. Conclusions: A single dose of mRNA vaccine after SARS-CoV-2 infection resulted in the highest observed nAb response. Two doses of mRNA vaccine in previously uninfected participants resulted in higher nAbs to SARS-CoV-2 than after 1 dose of vaccine or SARS-CoV-2 infection alone. nAb response also differed by mRNA vaccine product. Abstract : One dose of mRNA COVID-19 vaccine after previous SARS-CoV-2 infection produced the highest neutralizing antibody titers; among those without history of infection, 2 doses of mRNA vaccine produced the most robust response.